Inkheart - Funke, Cornelia Caroline (New York : Scholastic, 2007)
Twelve-year-old Meggie learns that her father Mo, a bookbinder, can "read" fictional characters to life when an evil ruler named Capricorn, freed from the novel "Inkheart" years earlier, tries to force Mo to release an immortal monster from the story.
Translation of: Tintenherz.
Originally published: Hamburg, Germany : C. Dressler Verlag, 2003.
Includes preview of Inkdeath.
Keywords: Books and reading -- Juvenile fiction; Characters and characteristics in literature -- Juvenile fiction; Magic -- Juvenile fiction; Bookbinding -- Juvenile fiction; Authorship -- Juvenile fiction; Books and reading -- Fiction; Characters in literature -- Fiction; Magic -- Fiction; Bookbinding -- Fiction; Authorship -- Fiction; Fantasy; Italy -- Fiction; Fantasy fiction